Penerapan CBIS Untuk Mendukung Keputusan Manajemen dalam Menghitung Index Kinerja Karyawan PT Devrindo Wydia Karawang Menerapkan Preference Selection Index - Darojat, Tubagus Ahmad (STMIK Budi Darma, 2020)
In this study, the authors applied a method in the computer information base system (CBIS), the Preference Selection Index, or known as the PSI method. It aims to produce a preference index of each employee, which later the index value is used as a measure of employee performance so it is known as the Employee Performance Index. Alternative data from the study the author uses 30 data as samples to be calculated Employee Performance Index. In addition to employee data, the author also uses several criteria in measuring the Employee Performance Index, such as discipline, loyalty, years of service, sanctions and reprimands, education. These criteria greatly affect the assessment of employee performance index. It is expected that the results of the measurement provide the right decision for employees in calculating the Employee Performance Index.